2018
DOI: 10.1016/j.jcms.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Bone-anchored maxillary protraction to correct a class III skeletal relationship: A multicenter retrospective analysis of 218 patients

Abstract: This study evaluated the impact of class III correction by elastic traction on four miniplates and the failure rate of bone-anchored miniplates in nonsyndromic patients. A total of 218 patients (112 males and 106 females; average 11.4 years), treated by 38 orthodontists, received four miniplates (total 872 miniplates) from 2008 to 2016 at three maxillofacial centers in two countries. Factors affecting the success and failure of the miniplates were retrospectively examined and skeletal changes on cephalometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
1
13
0
5
Order By: Relevance
“…Currently, the most common orthopedic treatment in both cleft and non-cleft patients with a Class III malocclusion is facemask therapy (FM) with or without rapid maxillary expansion (RME). This tooth-borne treatment modality, often used in patients with early deciduous or early mixed dentition [11,12], has been reported to have undesirable side effects such as dentoalveolar compensation and a clockwise rotation of the mandible [13,14]. These side effects are caused by the induced orthopedic force, which is not transferred directly to the circum-maxillary sutures, but directly or partially on the dentition.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most common orthopedic treatment in both cleft and non-cleft patients with a Class III malocclusion is facemask therapy (FM) with or without rapid maxillary expansion (RME). This tooth-borne treatment modality, often used in patients with early deciduous or early mixed dentition [11,12], has been reported to have undesirable side effects such as dentoalveolar compensation and a clockwise rotation of the mandible [13,14]. These side effects are caused by the induced orthopedic force, which is not transferred directly to the circum-maxillary sutures, but directly or partially on the dentition.…”
Section: Introductionmentioning
confidence: 99%
“…15 This finite element analysis study showed high von Mises stresses at the sites of miniplate placement in both maxilla and mandible, but in much less magnitude at the mandibular miniplate attachment site. A previous study by Van Hevele et al 16 showed that the failure of miniplates was six times more frequent in the maxilla, and occurred at a faster rate in the maxilla than in the mandible. This evidence was validated by the present study, in which the mandible showed approximately one-fourth of von Mises stress when compared to the maxilla.…”
Section: Discussionmentioning
confidence: 95%
“…Para esto, colocaron cuatro mini placas en los maxilares y dos semanas después fueron activadas con una fuerza inicial de 300 gr por lado con elásticos intermaxilares, la cual se incrementó un mes después a 350 gr, dos meses después a 450 gr, con un total de tratamiento de 12 meses y en la comparativa cefalométrica, demostró aumento en la proinclinación de los incivos superiores, resultados similares a los obtenidos en el presente caso clínico. 18 Por otra parte, J.Van Hevele y cols., 19 realizó un estudio en 218 pacientes entre 9 y 14 años para evaluar los efectos de las mini placas en pacientes clase III; después de 14 días de la colocación, empezo la tracción con una fuerza de 100 gr por lado y fue aumentando semanalmente hasta lograr una fuerza máxima de 250 gr por lado; donde obtuvieron un éxito del 93.6%. 19 Resultados similares a los reportados por Cevidanes y cols.., 20 en su estudio realizado en pacientes en étapa prepuberal entre los 11 y 12 años; a quienes les colocaron cuatro mini placas modificadas: Dos en el maxilar y dos en la mandíbula; fueron activadas tres semanas después de su colocación con una fuerza inicial de 150 gr por lado, al segundo mes 200 gr y al tercer mes 250 gr; con una duración total de 12 meses.…”
Section: Discussionunclassified
“…18 Por otra parte, J.Van Hevele y cols., 19 realizó un estudio en 218 pacientes entre 9 y 14 años para evaluar los efectos de las mini placas en pacientes clase III; después de 14 días de la colocación, empezo la tracción con una fuerza de 100 gr por lado y fue aumentando semanalmente hasta lograr una fuerza máxima de 250 gr por lado; donde obtuvieron un éxito del 93.6%. 19 Resultados similares a los reportados por Cevidanes y cols.., 20 en su estudio realizado en pacientes en étapa prepuberal entre los 11 y 12 años; a quienes les colocaron cuatro mini placas modificadas: Dos en el maxilar y dos en la mandíbula; fueron activadas tres semanas después de su colocación con una fuerza inicial de 150 gr por lado, al segundo mes 200 gr y al tercer mes 250 gr; con una duración total de 12 meses. 20 En algunos pacientes reportan que hubo interferencias oclusales durante el tratamiento, por lo que decidieron colocar un paladar con pistas planas y concluyeron que permitió una mejor tracción.…”
Section: Discussionunclassified